Parcelamento, edificação e utilização compulsórios de imóveis públicos urbanos - Levin, Alexandre (2008)
The enactment of the Brazilian urban law referred to as Estatuto da Cidade, or Urban Act (Brazilian Law 10.257/2001), was a landmark in the affirmation and development of Brazilian Urban Law. Said statute established the guidelines for urban policy, and provided for the tools aimed at achieving the stated goals. The guideline highlighted in this paper is the fight against the speculative retention of urban real properties. Such speculation activity most of the time stems from the underutilization or non-utilization of the urban real property. One waits for the occasional increase in the value of the property, often as a result of investments made by the very Public Administration, to sell it afterwards at a price significantly higher than that at which it was bought, without having to worry about the social harm caused by such practice, and clearly infringing the constitutional principle that provides for the social function of the property. This form of retaining urban real property is deleterious to urban planning, the basis of which is the statute that introduces the municipal zoning ordinance. Such ordinance sets the criteria for the assessment of the lawful use of urban real estate. If the property is not used in accordance with the terms provided for by it, legal and constitutional remedies may be applied in order to compel the owner to fit his property to the terms stipulated by the zoning ordinance, which sets the parameters for the assessment of the regular use of urban real properties. If the property does not comply with the legal prescriptions, legal and constitutional measures may be applied in order to compel the owner to arrange for its property to follow the zoning ordinance legislation. Among such measures, one approached the mandatory parceling, building, and use of urban property, the graduated real estate tax, and the expropriation paid with government bonds, all of which are provided for in the Federal Constitution and in the Urban Act, and grounded on the social function of property. The main objective of this paper, however, was the analysis of the possible application of such measures to the public urban property that fails to comply with the rules provided for by the city zoning ordinance. For this purpose, one sought to prove, based on the Federal Constitution and the urban law, the possibility of application of the principle that stipulates the social function of property also to public urban real properties which fail to meet the prescriptions set by the city zoning ordinance. Finally, one demonstrated that there are no legal reasons for the non-application of said zoning-ordinance measures to public properties. Otherwise, one would cause the rules of urban planning to be violated and thus prejudice the fulfillment of the social functions of the city, which is the primary objective of urban policy, and guaranteed by the Federal Constitution